Blood-Derived microRNAs for Pancreatic Cancer Diagnosis: A Narrative Review and Meta-Analysis - Li, Xiaodong; Gao, Pujun; Wang, Yang; Wang, Xiaocong (Frontiers in Physiology, 2018)
MicroRNAs (miRNAs) have been reported to be aberrantly expressed in patients with pancreatic cancer. In present review we explored the biological roles of miRNAs in pancreatic cancer and their clinical value in diagnosis. In the systematic review, the potential value of miRNAs as biomarkers was investigated by reviewing the altered miRNA profiles reported in pancreatic cancer patients in 356 included studies. In the subsequent meta-analysis, we included 17 studies in early diagnosis of pancreatic cancer with a panel of altered miRNAs. The following results were obtained: pooled sensitivity of 0.88 (95% confidence interval [CI] 0.83–0.92), pooled specificity of 0.83 (95%CI 0.77–0.88), diagnostic odds ratio of 27 (95%CI 14–53), and area under the receiver operating characteristic curve of 0.90 (95%CI 0.88–0.93). In conclusion, our findings suggest that aberrant miRNA expression in blood play an essential role in pancreatic cancer, and meta-analysis revealed blood-derived miRNAs as probable biomarkers for early diagnosis of pancreatic cancer.